Brucellosis in Humans and Animals. - Corbel, Michael J. (World Health Organization, 2006)
Brucellosis, also known as ''undulant fever, ''Mediterranean fever'' or ''Malta fever'' is an important human disease in many parts of the world. It is a zoonosis and the infection is almost invariably transmitted to people by direct or indirect contact with infected animals or their products. These Guidelines are designed as a concise, yet comprehensive, statement on brucellosis for public health, veterinary and laboratory personnel without access to specialized services. They are also to be a source of accessible and updated information for such others as nurses, midwives and medical assista.